LEGAL ANALYSIS OF PRODUCTS, SERVICES AND SERVICE QUALITY IN INFLUENCING CUSTOMER SATISFACTION AT BANK SYARIAH MANDIRI IN JAYAPURA CITY - Pelupessy, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research, entitled "Legal Analysis of Products, Services, and Service Quality in Influencing Customer Satisfaction at Bank Syariah Mandiri in Jayapura City," aims to identify and analyze the influence of products, services, and service quality on customer satisfaction at Bank Syariah Mandiri in Jayapura City. This study also aims to identify and analyze the steps taken by Bank Syariah Mandiri to ensure customer satisfaction with the services provided by the bank to the community in Jayapura City. The method used in this research is normative and empirical juridical, an approach that refers to laws, literature, written regulations, or other secondary legal materials and identifies and conceptualizes law as a real social institution within the real-life system. The output of this research is to contribute legal thought and knowledge to Bank Syariah Mandiri and the community in Jayapura City regarding how products, services, and service quality can influence customer satisfaction at Bank Syariah Mandiri in Jayapura City.